The efficacy of early progressive resistance exercise in the postoperative management of pancreaticoduodenectomy for pancreatic cancer: a randomized controlled trial - Liu, Xuexue; Shi, Neng; Li, Rui; Song, Yuan (Frontiers in Surgery, 2025)
BackgroundEnhanced Recovery After Surgery (ERAS) is of significant importance to the prognosis of patients with pancreatic cancer who have undergone pancreaticoduodenectomy. This study aims to analyze the efficacy of early progressive resistance exercise in the postoperative management of pancreaticoduodenectomy for pancreatic cancer, thereby providing evidence-based support for clinical treatment and nursing.MethodsThis study enrolled patients who underwent pancreaticoduodenectomy for pancreatic cancer at our hospital from January 2023 to December 2024. Participants were randomized into two groups using a random number table: the progressive resistance exercise group and the control group. The control group received standard care, while the progressive resistance exercise group underwent the progressive resistance exercise protocol in addition to standard care.ResultsA total of 80 patients who underwent pancreaticoduodenectomy for pancreatic cancer were included in the study, with 40 patients assigned to each group. Progressive resistance exercise significantly reduced the time to first water intake, time to first food intake, time to first ambulation, and duration of hospital stay (all p < 0.05). Post-intervention, the EORTC QLQ-C30 scores increased in both groups, with the progressive resistance exercise group achieving significantly higher scores (p < 0.05). Concurrently, the VAS and PSQI scores decreased in both groups, with the progressive resistance exercise group exhibiting significantly lower scores (p < 0.05). Scores for emotional state, physical comfort, psychological support, self-care ability, and pain all improved post-intervention, with the progressive resistance exercise group showing significantly higher scores (p < 0.05). Additionally, the incidence of urinary retention was significantly lower in the progressive resistance exercise group (p = 0.011).ConclusionProgressive resistance exercise has been demonstrated to effectively promote functional recovery and overall rehabilitation in patients with pancreatic cancer following pancreaticoduodenectomy. Given its significant benefits, the integration of progressive resistance exercise into clinical practice and nursing protocols is recommended.